1997
DOI: 10.1536/ihj.38.163
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Involvement in Progressive Muscular Dystrophy of the Duchenne Type.

Abstract: SUMMARYDuchenne's progressive muscular dystrophy (DMD) is a genetic muscle disorder that causes degeneration and atrophy of the systemic and cardiac muscle. The disease is manifested early in childhood, and most of patients die by age 20 years of respiratory failure or heart failure. The cardiac involvement in DMD is characterized pathologically by degeneration and fibrosis of the myocardium, centering around the posterolateral wall of the left ventricle. Functionally, an abnormal electrocardiogram, valve moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 88 publications
0
11
0
3
Order By: Relevance
“…This suggests acquired deterioration in b-adrenoreceptor responses. As the most frequent cardiac abnormality in DMD is sinus tachycardia occurring from childhood and persisting throughout life even in wheelchair-bound patients, 30 this finding in mdx mice presents somewhat of a contradiction, particularly as basal heart rates did not differ between strains in any age group. Autonomic defects have been reported in both the mdx model and patients with DMD.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests acquired deterioration in b-adrenoreceptor responses. As the most frequent cardiac abnormality in DMD is sinus tachycardia occurring from childhood and persisting throughout life even in wheelchair-bound patients, 30 this finding in mdx mice presents somewhat of a contradiction, particularly as basal heart rates did not differ between strains in any age group. Autonomic defects have been reported in both the mdx model and patients with DMD.…”
Section: Discussionmentioning
confidence: 99%
“…5,25,34,35). Fibrotic lesions are thought to result from myocyte necrosis and subsequent inflammatory response.…”
Section: Grmdmentioning
confidence: 99%
“…14 The cardiac involvement in DMD is characterized pathologically by degeneration and fibrosis of the myocardium, centering around the posterolateral wall of the left ventricle. 15 Myocardial fibrosis was observed in most of the patients with DMD in an autopsy study. 16 Autopsy studies have shown that cardiomyopathy of Duchenne's muscular dystrophy (DMD) is characterized by fibrosis of the posterobasal and contiguous lateral wall of the left ventricle.…”
Section: Author's Replymentioning
confidence: 96%